Victorian Arts and the Challenge of Modernity: Analogy, the Grid, and Chemical Transformations - Francesca Orestano (Cahiers Victoriens et Edouardiens)
My article has its point of departure among the artists of the 20th-century avant-garde, who worked with a distinct awareness of their modernity and yet adopted an intellectual vantage point that enlarged their vision, to the extent of allowing them to embrace at once modern art and the art of the Neolithic age. Among them T. S. Eliot, James Joyce, Virginia Woolf, Roger Fry, who variously responded to the drawings of Magdalenian artists, or to the art of Homer, while having recourse to modern science, chemistry especially, in order to explain literary phenomena. Such views are examined by focusing on the transformative power of the arts in Victorian and Edwardian culture and society. The article investigates such a scenario by dwelling first on the epistemic horizon in which science, art and literature conspire together to mould the modern mind. Subsequently the article moves à rebours, in order to suggest the possible reasons for such hermeneutic proximity. The strategy that allows the artists and critics to move forward and backwards in time is due to their insistence on analogy, which allows them to examine side by side the very modern and the very old. In addition to analogy, optical technology allows them to assess art from a visual point of view, thus emphasizing formal values: in sum the tools adopted have their symbolic and practical equivalent in chemistry. Such are the transformative powers that promote intermedial dynamics among the arts, and they date back to Victorian times, where they appear under the shape of the grid. The grid is the container in which the achievements of Victorian culture, industry and art are ordered and organized. The grid provides the structure to the Crystal Palace housing the Great Exhibition in 1851, and the grid is the structure presiding over modern chemistry, owing to the tabular arrangement of chemical elements envisaged by Russian chemist Dmitri Mendeleev and first published in 1869. Such grids suggest that the epistemic width invoked by the avant-garde artists—its wide connective capability, its conceptual emphasis on analogy among a variety of different experiences—can be traced back to the Victorian and Edwardian age.